AN OVERVIEW OF FINANCIAL LAW AS AN INDEPENDENT BRANCH OF THE LEGAL SYSTEM OF THE REPUBLIC OF BULGARIA - Savina Mihaylova Goleminova (Yustisia, 2019)
The present article aims to provide an overview of financial law as an independent branch of the legal system of the Republic of Bulgaria from a both historical and functional point of view, in the context of its traditions and current trends, which reflect the financial and legal system of the EU. The EU membership of Bulgaria holds numerous challenges and requires the mobilisation of the intellectual and physical potential of all stakeholders involved. Financial law is one of the most dynamic fields of legislation and case-law. The financial legal doctrine addresses the new challenges, building on constitutional, financial and administrative legal traditions and practices in the field of administrative justice in Bulgaria following the Tarnovo Constitution.